THE INFLUENCE OF DRIP IRRIGATION WITH LIMITEDLY AVAILABLE WATERS ON THE SALT COMPOSITION OF DARK CHESTNUT SOIL - Natalya E. Volkova; Svetlana V. Podovalova (Мелиорация и гидротехника)
Purpose: to assess the effect of drip irrigation with limitedly available waters on the salt composition of dark chestnut soil. Materials and methods. The studies were carried out in 2022–2024 on a pilot site in the Crimean region. The influence of the distance to the drip tape on the distribution of water-soluble salts in the soil, the change in the content of total and toxic salts, the degree of salinization and the chemistry of the soil extract during irrigation with limitedly available waters were studied. The quality of irrigation water was assessed according to the soil-ameliorative classification. Results. Significant variation in the content of water-soluble salts in the upper 20-cm soil layer was recorded with drip irrigation when laying a tape every 160 cm. The difference between the minimum and maximum values in 2023 was 0.6 %. The salinization process was most intense at a distance of 0–30 cm from the drip tape. In comparison with rainfed conditions, an accumulation of total and toxic salts was recorded closer to the middle of the row spacing, in a meter-thick soil layer, when using water with a mineralization of 2.6–3.1 g/l for irrigation; some of these salts were then washed out by autumn-winter precipitation into the underlying horizons. The use of better quality water resources in 2024 (mineralization of 1.1–1.4 g/l) contributed to a decrease in the level of negative impact on the soil, in comparison with 2023, but at the same time, an increase in the content of chlorine and sodium ions was noted during the growing season, as a result of which the degree of salinization changed (from non-saline to slightly saline) and the type of chemism (from chloride-sulfate to sulfate-chloride). Conclusions: the technological solutions implemented on the pilot site in 2022–2024 and represented by the use of drip irrigation and the transition to the use of limitedly available waters of better quality for irrigation purposes in 2024 are generally insufficient to prevent further development of soil salinization.